Documents and the history of early Islamic world: [3rd Conference of the International Society for Arabic Papyrology, Alexandria, 23-26 March 2006] - Schubert, Alexander T. (Islamic history and civilization, 2015)
1.2.3.4.5.6.7.8.9.10.11.12.13.14.15.Introduction /Administration & Government:A late Ayyubid report of death found at Quṣayr al-Qadīm /On the identity of Shahrālānyōzān in the Greek and Middle Persian papyri from Egypt /Le monastere de baouit et l'administration arabe /Fiscal evidence from the nessana Papyri /Commerce & Travel:Travel in Coptic documentary texts /Le transport de marchandises et de personnes sur le Nil en 823 A.H./1420 È.C. /Language & Culture:P. Cair. Arab. III 167: a discussion of the Akhmim declaration /Greek and Arabic in Nessana /The master spoke : take one of 'the sun' and one unit of almulgam": hitherto unnoticed coptic papyrological evidence for early Arabic alchemy /Terms for vessels in Arabic and Coptic documentary texts and their archaeological and ethnographic correlates /A Qurānic amulet on papyrus: P. Utah. Ar. 342 /New Editions & Collections:Les papyrus arabes de Heidelberg disparus : essai de reconstruction et d'analyse /Two new Arabic editions : a land survey from ihnās and ḥadīths concerning funerary practice /Sunshine wine on the Nile /Hugh Kennedy --Anne Regourd;Jairus Banaji;Alain Delattre;Shaun O'Sullivan --Anna Selander;Frédéric Bauden --Mostafa El-Abbadi;Rachel Stroumsa;Tonio Sebastian Richter;Tascha Vorderstrasse;Matt Malczycki --R.G. Khoury;Alia Hanafi;Nicole Hansen.
Text teilw. engl., teilw. franz
Keywords: Quelle; Konferenzschrift; Konferenzschrift -- 2006 -- Alexandria; Geschichte 600-1400; Handschrift; Geschichte; Islam